APPLICATION OF THE CERTAINTY FACTOR METHOD IN DIAGNOSIS DAMAGE TO WEB-BASED DSLR CAMERA - Benyamin Baro Bulu; Andreas Ariyanto Rangga; Maria Wilda Malo (CV. Fahr Publishing, 2023)
system to pass the light beam to both places, namely the Focal Plane and Viewfinder, thus allowing the photographer to be able to see objects through the camera exactly the same as the photo. used sometimes experience several problems such as minor damage or even heavy damage. There are two types of camera damage, namely damage to the hardware device (both lens and camera body) and software. Therefore, the author attempts to conduct research on an expert system for diagnosing damage to web-based DSLR cameras using the certainty factor method to measure the level of certainty regarding a damage. The results of the expert system for diagnosing damage to DSLR cameras are to design a system that can provide a consultation facility for DSLR camera photographers in diagnosing damage to DSLR cameras. The system can recognize damage correctly and provide results in percentage form if there is more than one damage result and the system able to provide information on whether a damaged camera device can be repaired or replaced with a new one.